Konsep Pengenaan Pajak Alat Berat Pasca Putusan Mahkamah Konstitusi Nomor 15/PUU-XV/2017 - Dahliana Hasan (Fakultas Hukum Universitas Islam Indonesia, 2021)
Constitutional Court Decision No. 15/PUU-XV/2017 opens up opportunities for the imposition of taxes on heavy equipment with a new legal basis through amendments to Law no. 28 of 2009 on Regional Taxes and Levies. Therefore, legislators need to think about the right concept of tax on heavy equipment, especially with regard to the environmental impacts caused as a result of its operation. This is a normative legal research using case study and conceptual approaches wtih qualitative analysis. This study concludes that the proposed heavy equipment tax concept is directed at restructuring the fuel tax policy and formulating a new concept for heavy equipment tax or registration fees that can become agents of pollution behavior change. However, both legislators and executors need to anticipate the main challenges that may arise in restructuring and implementing the tax policy.